NaIO4-KI-NaN3 as a new reagent system for C-H functionalization in hydrocarbons - Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2008)
The NaIO4-KI-NaN3 combination has been found to be an efficient, reliable, and inexpensive reagent system for mono- and 1,2-difunctionalization of hydrocarbons via C-H bond activation to afford vicinal azido- and acetoxy iodinations of cyclic hydrocarbons. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: azides; C-H activation; Iodination; NaIO4